Effects of adding Allium mongolicum Regel powder and yeast cultures to diet on rumen microbial flora of Tibetan sheep (Ovis aries) - Wang, Chunhui; Fan, Juan; Ma, Keyan; Wang, Huihui; Li, Dengpan; Li, Taotao; Ma, Youji (Frontiers in Veterinary Science, 2024)
The purpose of this experiment was to study the effect of Allium mongolicum Regel powder (AMR) and yeast cultures (YC) on rumen microbial diversity of Tibetan sheep in different Ecological niche. Forty male Tibetan sheep lambs with an initial weight of 18.56±1.49 kg(6 months old) were selected and divided into four groups (10 sheep/pen;n=10. Each animal was grazed for 8 hours per day(Control Group), each animal was supplemented with 200 g of concentrate per day(Group I), each animal was supplemented with 200 g of concentrate and 10 g of AMR per day(Group II), each animal was supplemented with 200 g of concentrate and 20 g of YC per day(Group III). The experiment lasted for 82 days, which consisted of 7 days of per-feeding period and 75 days of formal period. The results indicated that: at the phylum level, the abundance of Bacteroidota and Verrucomimicrobiota in L-Group II and L-Group III were increased, while the abundance of Proteobacteria was decreased in the LA(Liquid-Associated), The proportion of F/B in S-Group II and S-Group III was increased compared to S-Group I and S-CON in the SA(Soild-Associated); At the genus level, the abundance of uncultured_rumen_bacterium and Eubacterium_ruminantium_group of L-Group II and L-Group III were increased, as the abundance of Rikenellaceae_RC9_gut_group was decreased in the LA ,the abundance of Prevotella and Eubacterium_ruminantium_group were increased in the S-Group II and S-Group III compared to S-Group I and S-CON, and the abundance of probable_genus_10 was the highest in S-Group II in the SA. After the addition of YC and AMR, there was an increase in rumen microbial abundance, which was found to be beneficial for the stability of rumen flora and had a positive impact on rumen health.